The whole yields more - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The relatively young Kenyan NGO SACRED-Africa (see Spore 82, page 15) is extending its work to improve maize-legume inter-cropping in ways that can be quickly adopted by farmers. SACRED stands, incidentally, for Sustainable Agriculture Centre for...